(untitled) (Journal of Asian Development Studies, 2025)
Greenfield investment allows for better risk management of environmental and social issues, as well as the development of opportunities that provide a rate of return connected to environmental benefits and offer greater accounting. This study explores the dynamic relationship between greenfield investment, GDP per capita and its square, human capital, governance, and environmental performance across 40 Asian countries from 2003 to 2020. Using the panel ARDL modeling approach, the analysis draws on secondary data from WDI, UNCTAD, and PWT. The findings reveal that greenfield investment positively influences environmental performance in Asia-Pacific. Moreover, human capital and governance also show a positive relationship with environmental performance, while GDP per capita has a negative effect. These results carry important policy implications that promoting greenfield investment can enhance environmental sustainability in Asian countries.